Asuhan keperawatan pada lansia dengan hipertensi - Annisa, Aulia Savira; Khairani, Khairani; Nurhasanah, Nurhasanah (Indonesian Journal of Health Science, 2024)
Background: Along with the aging process, the body gradually undergo various changes and health problems, one of which is hypertension. Hypertension is commonly referred to the silent killer as it is a deadly disease, with complications which can increase the risk of heart attack, heart failure, stroke and kidney failure. Management of hypertension consists of pharmacological therapy and non-pharmacological therapy. Aim of  Research: This study aims to provide an overview of nursing care for erderly with hypertension problems. Research Method: This research uses a case study conducted by home visit. Results of Study: The results of the evaluation showed that having the increase knowledge related to controlling hypertension, being able to apply DASH and reducing blood pressure from 165/95 mmHg to 142/89 mmHg. Conclusion: After being given the intervention, erderly and families showed an increase in knowledge about hypertension, being able to apply DASH in everyday life and being able to carry out complementary therapies to reducing blood pressure. Latar Belakang: Seiring dengan proses penuaan, tubuh akan mengalami berbagai perubahan dan masalah kesehatan, salah satunya adalah hipertensi. Hipertensi sering disebut sebagai silent killer karena hipertensi termasuk penyakit yang mematikan, dengan komplikasi yang dapat meningkatkan resiko serangan jantung, gagal jantung, stroke dan gagal ginjal. Tujuan: Penelitian ini bertujuan untuk memberikan Gambaran tentang asuhan keperawatan pada lansia dengan hipertensi. Metode: Penelitian ini menggunakan studi kasus yang dilakukan dengan kunjungan rumah (home visit). Hasil: Hasil evaluasi pengetahuan terkait pengendalian hipertensi meningkat, mampu menerapkan DASH dan terjadi penurunan tekanan darah dari 165/95 mmHg menjadi 142/89 mmHg. Kesimpulan: Setelah diberikan intervensi, lansia dan keluarga menunjukkan adanya peningkatan pengetahuan tentang pengendalian hipertensi, menerapkan DASH dalam kehidupan sehari-hari dan dapat melaksanakan terapi komplementer untuk menurunkan tekanan darah.